THE EFFECT OF DEBT TO ASSET RATIO, CASH POSITION AND FIRM SIZE ON DIVIDEND PAYOUT RATIO WITH PROFITABILITY AS MEDIATION VARIABLES IN THE PROPERTY AND REAL ESTATE SECTOR IN THE INDONESIA STOCK EXCHANGE IN 2016 – 2019 - Jesslyn Kosasih; Nagian Toni; Widya Sari (AGUSPATI Research Institute, 2022)
In the property and real estate industries on the Indonesia Stock Exchange from 2016 to 2019, this study intends to evaluate and analyze the effect of Debt to Asset Ratio, Cash Position, and Firm Size on the Dividend Payout Ratio with Profitability as a mediating variable. The population for this study will be property and real estate companies that have been listed on the Indonesia Stock Exchange for at least four years. Purposive sampling was the method adopted in this study. A deductive strategy was applied in the research. The data collection technique employed in this study was a documentation study, and the type of data used was secondary data. The data is processed using the SmartPLS application and the Partial Least Square data analysis approach is used in this study. The findings of this study show that debt to asset ratio and firm size have no impact on dividend payout ratio, however cash position has a positive impact. The study's findings also reveal that profitability has no effect on the dividend payout ratio when debt to asset ratio, cash position, or business size are taken into account. It is advised that other mediating variables such as business value be replaced in future studies.